A nano-array composite photocatalyst based on a metal organic framework material and a preparation method thereof
Patent Information
- Application Number
- CN202310560125.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-05-18
AI Technical Summary
但是,目前光催化转化CO2的反应效率依然较低,产物复杂、选择性较差,且催化剂制备调节方法依然面临着许多挑战,因此,高性能异质结光催化的开发制备成为本领域亟待解决的重要问题之一
[0019] This invention enables the in-situ growth of Ni-BDC nanosheet arrays on a FTO conductive glass matrix. Ni-BDC consists of numerous flat and large nanosheets, resembling a "nanoforest," interconnected to form a macroporous structure. This structure spreads out on the FTO, increasing the specific surface area, which is beneficial for CO2 adsorption. Furthermore, the presence of NH2-MIL-125 with good light absorption prevents aggregation. The constructed heterojunction structure enhances light capture and visible light utilization, increases the specific surface area, exposes more active sites, and achieves efficient phase-to-phase separation of photogenerated electron-hole pairs. In addition, the preparation method of this invention is simple, easy to implement, has high yield, and is suitable for mass production.
Smart Images

Figure CN116586116B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst research and preparation technology, and particularly relates to a nanoarray composite photocatalyst based on metal-organic framework materials and its preparation method. Background Technology
[0002] The rising levels of greenhouse gases such as CO2 in the atmosphere and the massive consumption of fossil fuels have drawn close attention to global climate change and future energy supply issues, forcing the development of new clean energy sources to reduce greenhouse gas emissions. To date, various CO2 conversion technologies have been developed, primarily including thermocatalysis, electrocatalysis, photocatalysis, biocatalysis, and photoelectrocatalysis. Among these methods, photocatalytic CO2 reduction mimics natural photosynthesis, combining the CO2 reduction reaction with the H2O oxidation reaction to create a carbon-neutral cycle, offering a feasible solution to global energy and environmental problems. Compared to electrocatalysis, photocatalysis utilizes the inexhaustible energy source of solar energy. Photocatalysis operates under mild conditions, typically at room temperature and pressure, while thermocatalysis usually requires high temperature, high pressure, and hydrogen to drive the reaction. Photocatalysis uses H2O and CO2 as reactants, which are readily available, and the reaction produces no secondary pollution. Therefore, photocatalytic CO2 reduction, as a clean, carbon-neutral, and sustainable technology, is receiving increasing attention. However, the current photocatalytic conversion of CO2 still has low efficiency, complex products, poor selectivity, and the catalyst preparation and regulation methods still face many challenges. Therefore, the development and preparation of high-performance heterojunction photocatalysis has become one of the important problems that urgently need to be solved in this field.
[0003] Metal-organic frameworks (MOFs) are novel porous functional materials, crystalline materials with a periodic network structure formed by metal nodes (metal ions or clusters) and organic ligands linked by coordination bonds. Due to their often high porosity, large specific surface area, and tunable pore size and properties, MOFs have potential applications in adsorption separation, gas storage, sensing, and catalysis. Inspired by semiconductor photocatalysis, different materials are combined in the form of heterojunctions to optimize optical, electronic, and catalytic performance. To obtain more complex structures and functions, there is great interest in the preparation of MOF materials and composite materials containing various MOFs and other components. Therefore, developing novel MOF-based photocatalysts with high catalytic activity, good photogenerated electron-hole pair separation, wide photoresponse range, high product selectivity, and strong reactant trapping ability is of significant research value. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention proposes a nanoarray composite photocatalyst based on metal-organic framework materials and its preparation method. This invention involves in-situ growth of Ni-BDC nanosheets on an FTO matrix (fluorine-doped SnO2 conductive glass) and loading cubic NH2-MIL-125 to obtain a highly stable MOF-on-MOF nanosheet array material. The constructed heterojunction structure achieves efficient interphase separation of photogenerated electron-hole pairs through interfacial contact, effectively overcoming the shortcomings of common MOF-based materials such as narrow photoresponse range and high carrier recombination rate. Furthermore, the material prepared by this invention further increases the specific surface area of the composite material, making it possible to improve product selectivity through surface property optimization.
[0005] To achieve the above objectives, the present invention provides a nanoarray composite photocatalyst based on a metal-organic framework material, comprising an FTO matrix, a sheet-like Ni-BDC nanosheet array grown in situ on the surface of the FTO matrix, and NH2-MIL-125 loaded on the Ni-BDC nanosheet array.
[0006] This invention also proposes a method for preparing the above-mentioned nanoarray composite photocatalyst based on metal-organic framework materials, comprising the following steps:
[0007] (1) Ni-BDC nanosheet arrays are grown in situ on the surface of FTO matrix (fluorine-doped SnO2 conductive glass, referred to as FTO matrix);
[0008] (2) The FTO matrix with Ni-BDC nanosheet arrays grown in situ on the surface was immersed in NH2-MIL-125 synthesis solution and NH2-MIL-125@Ni-BDC was hydrothermally synthesized to obtain the nanoarray composite photocatalyst based on metal-organic framework material.
[0009] Furthermore, the FTO substrate selected in this invention is fluorine-doped SnO2 conductive glass, which has a smooth surface and, compared to substrates such as carbon paper and nickel foam, lacks a complex fibrous structure, resulting in a simpler structure and facilitating in-situ growth of MOFs on its surface. A comparison of Ni-BDC growth on indium tin oxide semiconductor (ITO) and ordinary glass slides revealed that Ni-BDC growth on the FTO substrate was better, with a higher loading capacity, forming a dense array of Ni-BDC nanosheets. Before use, the FTO substrate needs to be ultrasonically vibrated in anhydrous ethanol or methanol for 10 minutes to remove surface impurities, which is more conducive to loading NH2-MIL-125@Ni-BDC. Additionally, the size of the FTO substrate used each time is 1*2 cm. 2 To maintain consistency.
[0010] The present invention chooses to first grow Ni-BDC nanosheet arrays in situ on FTO matrix because its sheet structure can spread out better on the substrate and is less prone to accumulation. In contrast, the regular small cubes of NH2-MIL-125 have a small contact surface with FTO, making them less likely to be loaded on the substrate and more likely to accumulate into large blocks.
[0011] Further, step (1) specifically includes the following steps: dissolving metallic nickel salt and terephthalic acid in a mixed solution of N,N-dimethylformamide, water and anhydrous ethanol using ultrasound, then placing the FTO matrix into the mixed solution, transferring it to a reaction vessel for heating and reaction, cooling to room temperature, rinsing with ethanol and drying, so that the Ni-BDC nanosheet array grows in situ on the surface of the FTO matrix.
[0012] Furthermore, the molar ratio of the nickel salt to terephthalic acid is 1:1, and the volume ratio of water, anhydrous ethanol, and N,N-dimethylformamide is 1:1:(10-16), preferably 1:1:16. The concentration of terephthalic acid in the mixed solution is 0.03-0.04 mol / L, preferably 0.035 mol / L. Using too low an amount of N,N-dimethylformamide will lead to incomplete reaction and the formation of irregular particles, while using too high an amount will result in sheet-like accumulation, which is not conducive to the loading of other substances.
[0013] Furthermore, the heating temperature is 90-140℃, and the time is 6-24h. Preferably, the heating temperature is 120℃, and the time is 12h. Excessive temperature and excessive time will cause Ni-BDC to detach from the FTO matrix, while insufficient temperature and time will result in low loading and incomplete reaction.
[0014] Further, in step (2), the NH2-MIL-125 synthesis solution is obtained by dissolving metallic titanium salt and amino terephthalic acid in a mixed solution of N,N-dimethylformamide and methanol.
[0015] Furthermore, the concentration of aminoterephthalic acid is 10-30 mmol / L, preferably 12 mmol / L; the volume ratio of N,N-dimethylformamide to methanol is 1:9-9:1, preferably 7:3; and the feed-to-liquid ratio of aminoterephthalic acid, the mixed solution (a mixed solution of N,N-dimethylformamide and methanol), and the titanium salt is 0.22 g:10 ml:250 μL. A low amount of N,N-dimethylformamide leads to excessive reaction impurities, while a high amount of N,N-dimethylformamide results in irregular morphology of NH2-MIL-125.
[0016] Furthermore, the hydrothermal temperature is 120-150℃, and the heating time is 12-24h, preferably 120℃ and 12h.
[0017] This invention also proposes the application of the aforementioned metal-organic framework-based nanoarray composite photocatalyst in the catalytic reduction of carbon dioxide.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] This invention enables the in-situ growth of Ni-BDC nanosheet arrays on a FTO conductive glass matrix. Ni-BDC consists of numerous flat and large nanosheets, resembling a "nanoforest," interconnected to form a macroporous structure. This structure spreads out on the FTO, increasing the specific surface area, which is beneficial for CO2 adsorption. Furthermore, the presence of NH2-MIL-125 with good light absorption prevents aggregation. The constructed heterojunction structure enhances light capture and visible light utilization, increases the specific surface area, exposes more active sites, and achieves efficient phase-to-phase separation of photogenerated electron-hole pairs. In addition, the preparation method of this invention is simple, easy to implement, has high yield, and is suitable for mass production. Attached Figure Description
[0020] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:
[0021] Figure 1 The X-ray powder diffraction pattern of the nanoarray composite photocatalyst (NH2-MIL-125@Ni-BDC) prepared in Example 1 of this invention;
[0022] Figure 2 The images show the electron microscope scans of the FTO matrix used in Example 1, the FTO matrix loaded with Ni-BDC nanosheet array prepared in step (1) of Example 1, and the nanoarray composite photocatalyst prepared in Example 1. In the images, a is the FTO matrix, b is the FTO matrix loaded with Ni-BDC nanosheet array, and c is the nanoarray composite photocatalyst prepared in Example 1.
[0023] Figure 3 The N2 adsorption curve analysis results are for NH2-MIL-125@Ni-BDC prepared in Example 1, Ni-BDC prepared in Comparative Example 1, and NH2-MIL-125 prepared in Comparative Example 2.
[0024] Figure 4The graph shows the CO and CH4 yields of NH2-MIL-125@Ni-BDC prepared in Example 1, Ni-BDC prepared in Comparative Example 1, and NH2-MIL-125 prepared in Comparative Example 2, as well as the results of CO and CH4 production in carbon dioxide catalysis experiments. In the graph, A represents the amount of carbon dioxide reduced to methane, and B represents the amount of carbon dioxide reduced to carbon monoxide.
[0025] Figure 5 The graph shows the yield results of the catalysts prepared in Examples 1-3 and Comparative Examples 1-5 for the catalytic production of CO and CH4 from carbon dioxide. Detailed Implementation
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0030] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0031] This invention also proposes a method for preparing a nanoarray composite photocatalyst based on a metal-organic framework material, comprising the following steps:
[0032] (1) Ni-BDC nanosheet arrays are grown in situ on the surface of FTO matrix (fluorine-doped SnO2 conductive glass, referred to as FTO matrix);
[0033] (2) The FTO matrix with Ni-BDC nanosheet arrays grown in situ on the surface was immersed in NH2-MIL-125 synthesis solution and NH2-MIL-125@Ni-BDC was hydrothermally synthesized to obtain the nanoarray composite photocatalyst based on metal-organic framework material.
[0034] The FTO substrate selected in this invention is fluorine-doped SnO2 conductive glass, which has a smooth surface and, compared to substrates such as carbon paper and nickel foam, lacks a complex fibrous structure, resulting in a simpler structure and facilitating in-situ growth of MOFs on its surface. A comparison of Ni-BDC growth on indium tin oxide semiconductor (ITO) and ordinary glass slides revealed that Ni-BDC growth on the FTO substrate was better, with a higher loading capacity, forming a dense array of Ni-BDC nanosheets. Before use, the FTO substrate needs to be ultrasonically vibrated in anhydrous ethanol or methanol for 10 minutes to remove surface impurities, which is more conducive to loading NH2-MIL-125@Ni-BDC. Furthermore, the size of the FTO substrate used each time is consistent (1*2cm). 2 ).
[0035] Since the Ni-BDC nanosheet array has a sheet-like structure, it can spread out better on the FTO substrate and is less prone to stacking. In contrast, NH2-MIL-125 is a small cube with a regular morphology, and its contact surface with the FTO substrate is small, making it difficult to load on the FTO substrate and easy to stack into large lumps. Based on the above reasons, in the preparation process of the embodiments of the present invention, the Ni-BDC nanosheet array is first grown in situ on the FTO matrix, and then NH2-MIL-125@Ni-BDC is synthesized.
[0036] Step (1) of this embodiment specifically includes the following steps: dissolving metallic nickel salt and terephthalic acid in a mixed solution of N,N-dimethylformamide, water and anhydrous ethanol using ultrasound, then placing the FTO matrix into the mixed solution, transferring it to a reaction vessel and heating it for reaction, then cooling it to room temperature, rinsing it with ethanol and drying it, so that the Ni-BDC nanosheet array grows in situ on the surface of the FTO matrix.
[0037] Using too low a concentration of N,N-dimethylformamide will lead to incomplete reaction and the formation of irregular particles, while using too high a concentration will result in sheet-like accumulation, which is not conducive to the loading of other substances. For the above reasons, in the embodiments of the present invention, the volume ratio of water, anhydrous ethanol and N,N-dimethylformamide is 1:1:(10-16), preferably 1:1:16.
[0038] In this embodiment of the invention, the molar ratio of the nickel salt and terephthalic acid is 1:1, and the concentration of terephthalic acid in the mixed solution is 0.03-0.04 mol / L, preferably 0.035 mol / L.
[0039] Excessive temperature and time can cause Ni-BDC to detach from the FTO matrix, while insufficient temperature and time can lead to low loading and incomplete reaction. Based on these reasons, in this embodiment of the invention, the heating temperature is 90-140℃ and the time is 6-24h; preferably, the heating temperature is 120℃ and the time is 12h.
[0040] In step (2) of this embodiment of the invention, the NH2-MIL-125 synthesis solution is obtained by dissolving metallic titanium salt and aminoterephthalic acid in a mixed solution of N,N-dimethylformamide and methanol.
[0041] The small amount of N,N-dimethylformamide leads to excessive reaction impurities, while the large amount of N,N-dimethylformamide results in irregular morphology of NH2-MIL-125. Based on the above reasons, in this embodiment of the invention, the volume ratio of N,N-dimethylformamide to methanol is 1:9-9:1, preferably 7:3. The ratio of aminoterephthalic acid, mixed solution (mixed solution of N,N-dimethylformamide and methanol), and titanium salt is 0.22g:10ml:250μL, wherein the concentration of aminoterephthalic acid is 10-30mmol / L, preferably 12mmol / L.
[0042] In this embodiment of the invention, the temperature of the hydrothermal system is 120-150°C, and the heating time is 12-24 hours, preferably 120°C and 12 hours.
[0043] The nanoarray composite photocatalyst based on metal-organic framework material prepared in the embodiments of the present invention includes an FTO matrix, a sheet-like Ni-BDC nanosheet array grown in situ on the surface of the FTO matrix, and NH2-MIL-125 loaded on the Ni-BDC nanosheet array.
[0044] All raw materials used in the embodiments of this invention were purchased commercially.
[0045] In this embodiment of the invention, "room temperature" refers to "25±2℃".
[0046] The technical solution of the present invention will be further illustrated by the following embodiments.
[0047] Example 1
[0048] A method for preparing a nanoarray composite photocatalyst based on a metal-organic framework material includes the following steps:
[0049] (1) Weigh 96 mg (0.40 mmol) nickel chloride hexahydrate and 66 mg (0.40 mmol) terephthalic acid and dissolve them in 18 mL of a mixed solution consisting of N,N-dimethylformamide, water and anhydrous ethanol in a volume ratio of 16:1:1, so that the concentration of terephthalic acid in the mixed solution is 0.035 mol / L. Mix the solution with sonication and put the FTO matrix cleaned with ethanol into the mixed solution. Transfer the solution to a tetrafluoroethylene reactor and react at 120 °C for 12 h. Cool the solution to room temperature, rinse it with ethanol and dry it in a 60 °C oven to allow the Ni-BDC nanosheet array to grow in situ on the surface of the FTO matrix.
[0050] (2) Weigh 0.22 g (12.5 mmol, concentration 12 mmol / L) of aminoterephthalic acid and dissolve it in 10 mL of a mixed solution of N,N-dimethylformamide and methanol with a volume ratio of 7:3. Sonicate for 15 min, then add 250 μL of titanium isopropoxide and sonicate to disperse. Immerse the FTO matrix with Ni-BDC nanosheet arrays grown on the surface in situ in the above solution, transfer it to a polytetrafluoroethylene reactor, keep it at 120 °C for 12 h, cool it to room temperature, rinse it with methanol and N,N-dimethylformamide, dry it and synthesize NH2-MIL-125@Ni-BDC to obtain a nanoarray composite photocatalyst based on metal-organic framework material, denoted as NH2-MIL-125@Ni-BDC.
[0051] Example 2
[0052] A method for preparing a nanoarray composite photocatalyst based on a metal-organic framework material includes the following steps:
[0053] (1) Weigh 96 mg (0.40 mmol) nickel chloride hexahydrate and 66 mg (0.40 mmol) terephthalic acid and dissolve them in 12 mL of a mixed solution consisting of N,N-dimethylformamide, water and anhydrous ethanol in a volume ratio of 10:1:1, so that the concentration of terephthalic acid in the mixed solution is 0.03 mol / L. Mix the solution with sonication and put the FTO matrix cleaned with ethanol into the mixed solution. Transfer the solution to a tetrafluoroethylene reactor and react at 90 °C for 6 h. Cool to room temperature, rinse with ethanol and dry in a 60 °C oven to allow the Ni-BDC nanosheet array to grow in situ on the surface of the FTO matrix.
[0054] (2) Weigh 0.22 g (12.5 mmol, concentration 10 mmol / L) of aminoterephthalic acid and dissolve it in 10 mL of a mixed solution of N,N-dimethylformamide and methanol with a volume ratio of 9:1. Sonicate for 15 min, then add 250 μL of titanium isopropoxide and sonicate to disperse. Immerse the FTO matrix with Ni-BDC nanosheet arrays grown on the surface in situ in the above solution, transfer it to a polytetrafluoroethylene reactor, keep it at 140 °C for 20 h, cool it to room temperature, rinse it with methanol and N,N-dimethylformamide, and dry it to synthesize NH2-MIL-125@Ni-BDC, and obtain a nanoarray composite photocatalyst based on metal-organic framework material.
[0055] Example 3
[0056] A method for preparing a nanoarray composite photocatalyst based on a metal-organic framework material includes the following steps:
[0057] (1) Weigh 96 mg (0.40 mmol) nickel chloride hexahydrate and 66 mg (0.40 mmol, concentration of 0.04 mol / L) terephthalic acid and dissolve them in 16 mL of a mixed solution consisting of N,N-dimethylformamide, water and anhydrous ethanol in a volume ratio of 14:1:1, so that the concentration of terephthalic acid in the mixed solution is 0.04 mol / L. Mix the solution with sonication and put the FTO matrix cleaned with ethanol into the mixed solution. Transfer the solution to a tetrafluoroethylene reactor and react at 140 °C for 24 h. Cool to room temperature, rinse with ethanol and dry in a 60 °C oven to allow the Ni-BDC nanosheet array to grow in situ on the surface of the FTO matrix.
[0058] (2) Weigh 0.22 g (12.5 mmol, concentration 30 mmol / L) of aminoterephthalic acid and dissolve it in 10 mL of a mixed solution of N,N-dimethylformamide and methanol with a volume ratio of 7.5:2.5. Sonicate for 15 min, then add 250 μL of titanium isopropoxide and sonicate to disperse. Immerse the FTO matrix with Ni-BDC nanosheet arrays grown on the surface in situ in the above solution, transfer it to a polytetrafluoroethylene reactor, keep it at 140 °C for 24 h, cool it to room temperature, rinse it with methanol and N,N-dimethylformamide, and dry it to synthesize NH2-MIL-125@Ni-BDC, and obtain a nanoarray composite photocatalyst based on metal-organic framework material.
[0059] Comparative Example 1
[0060] A method for preparing a photocatalyst includes the following steps:
[0061] 96 mg (0.40 mmol) of nickel chloride hexahydrate and 66 mg (0.40 mmol) of terephthalic acid were weighed and dissolved in 18 mL of a mixed solution consisting of N,N-dimethylformamide, water, and anhydrous ethanol in a volume ratio of 16:1:1, so that the concentration of terephthalic acid in the mixed solution was 0.035 mol / L. The mixture was ultrasonically mixed, and the FTO matrix cleaned with ethanol was placed into the mixed solution. The mixture was then transferred to a tetrafluoroethylene reactor and reacted at 120 °C for 12 h. After cooling to room temperature, the mixture was rinsed with ethanol and dried in a 60 °C oven, so that the Ni-BDC nanosheet array grew in situ on the surface of the FTO matrix, denoted as Ni-BDC.
[0062] Comparative Example 2
[0063] A method for preparing a photocatalyst includes the following steps:
[0064] Weigh 0.22 g (12.5 mmol, concentration 12 mmol / L) of aminoterephthalic acid and dissolve it in 10 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 7:3. Sonicate for 15 min, then add 250 μL of titanium isopropoxide and sonicate to disperse. Immerse the FTO matrix in the above solution, transfer it to a polytetrafluoroethylene reactor, and keep it at 120 °C for 12 h. Cool to room temperature, rinse with methanol and N,N-dimethylformamide, and dry to allow NH2-MIL-125 to grow in situ on the surface of the FTO matrix, denoted as NH2-MIL-125.
[0065] Comparative Example 3
[0066] Same as Example 1, except that the FTO matrix is replaced with an ITO matrix.
[0067] Comparative Example 4
[0068] Similar to Comparative Example 1, the only difference is that the FTO matrix is replaced with a regular glass slide.
[0069] Comparative Example 5
[0070] A method for preparing a photocatalyst includes the following steps:
[0071] (1) Weigh 0.22 g (12.5 mmol, concentration 12 mmol / L) of aminoterephthalic acid and dissolve it in 10 mL of a mixed solution of N,N-dimethylformamide and methanol with a volume ratio of 7:3. Sonicate for 15 min, then add 250 μL of titanium isopropoxide and sonicate to disperse. Soak the FTO matrix cleaned with ethanol in the above solution, transfer it to a polytetrafluoroethylene reactor, keep it at 120 °C for 12 h, cool it to room temperature, rinse it with methanol and N,N-dimethylformamide, and dry it so that NH2-MIL-125 grows in situ on the surface of the FTO matrix.
[0072] (2) Weigh 96 mg (0.40 mmol) nickel chloride hexahydrate and 66 mg (0.40 mmol, concentration of 0.035 mol / L) terephthalic acid and dissolve them in 18 mL of a mixed solution consisting of N,N-dimethylformamide, water and anhydrous ethanol in a volume ratio of 16:1:1. Mix the solutions by sonication and add the FTO matrix loaded with NH2-MIL-125 into the mixed solution. Transfer the solution to a tetrafluoroethylene reactor and react at 120 °C for 12 h. Cool the solution to room temperature, rinse with ethanol and dry in a 60 °C oven to obtain the composite photocatalyst.
[0073] Performance testing
[0074] I. Material Morphology Characterization
[0075] The X-ray powder diffraction pattern of the nanoarray composite photocatalyst (NH2-MIL-125@Ni-BDC) prepared in Example 1 is shown in Figure 1. Figure 1 .Depend on Figure 1 It can be seen that the nanoarray composite photocatalyst prepared in Example 1 contains XRD diffraction peaks of both NH2-MIL-125 and Ni-BDC, indicating the successful synthesis of the composite catalyst.
[0076] Electron microscopy was performed on the FTO matrix used in Example 1, the FTO matrix loaded with Ni-BDC nanosheet arrays prepared in step (1) of Example 1, and the nanoarray composite photocatalyst prepared in Example 1. The results are shown in the figure. Figure 2 Wherein, a is the FTO matrix, b is the FTO matrix loaded with Ni-BDC nanosheet arrays, and c is the nanoarray composite photocatalyst prepared in Example 1. Figure 2 It can be seen that the small cubic NH2-MIL-125 is well loaded on the nanosheet Ni-BDC, indicating that the morphology of Ni-BDC is not changed after NH2-MIL-125 loading and its own morphology is completely preserved, further demonstrating the successful preparation of the nanoarray composite catalyst.
[0077] N2 adsorption curves of NH2-MIL-125@Ni-BDC prepared in Example 1, Ni-BDC prepared in Comparative Example 1, and NH2-MIL-125 prepared in Comparative Example 2 were analyzed using a Bestar adsorption instrument at 77 K. The test results are shown in the figure. Figure 3 ,Depend on Figure 3 As can be seen, in Example 1, the N2 adsorption capacity increased significantly after loading NH2-MIL-125 onto Ni-BDC, and the specific surface area increased from 27.8457 m² / g. 2 / g(Ni-BDC) increased to 467.8938m 2 / g(NH2-MIL-125@Ni-BDC) exposes more active sites, which is more conducive to CO2 conversion.
[0078] II. Characterization of Catalytic Performance
[0079] The catalysts used were NH2-MIL-125@Ni-BDC prepared in Example 1, Ni-BDC prepared in Comparative Example 1, and NH2-MIL-125 prepared in Comparative Example 2, respectively. A 300W xenon lamp was used as the light source for the photocatalytic experiment, and the light radiation intensity was 150mW / cm². 2 The reactor was initially filled with high-purity carbon dioxide gas and rinsed ten times to obtain the reaction gas. It was then equilibrated in the dark for one hour at a pressure of 0.1 MPa, followed by illumination. Samples were taken at 2, 4, and 6 hours, and the results were analyzed by gas chromatography. The products at different time points were analyzed using an Agilent gas chromatograph. The percentages of CO and CH4 gases in the total gas content were substituted into the equation PV = nRT (where V represents the total volume of the reactor, 0.05 m³). 3 The calculated yields of CO and CH4 are shown in the figure. Figure 4 Where A represents the amount of carbon dioxide reduced to methane, and B represents the amount of carbon dioxide reduced to carbon monoxide. To provide a more direct comparison of the performance test results of the products from Examples 1-3 and Comparative Examples 1-5, products after 6 hours of reaction were selected for analysis and comparison. The analytical results are as follows: Figure 5 As shown.
[0080] Depend on Figure 4 and Figure 5It can be seen that the CH4 and CO yields catalyzed by NH2-MIL-125@Ni-BDC prepared in Example 1 of this invention are the highest. This is because the type I heterojunction formed by the combination of Ni-BDC and NH2-MIL-125 promotes the effective separation of electrons and holes. Ni-BDC is composed of many flat and large nanosheets, like a "nanoforest", which are interconnected to form a macroporous structure. It spreads out on FTO, which increases the specific surface area and is conducive to CO2 adsorption. It also supports NH2-MIL-125 with good light absorption to avoid accumulation. The constructed heterojunction structure increases the capture of light and the utilization of visible light, increases the specific surface area, exposes more active sites, realizes the efficient phase separation of photogenerated electron-hole pairs, and improves catalytic performance. Comparative Examples 1 and 2 show low light utilization rates for single Ni-BDC and NH2-MIL-125, with easy electron-hole recombination leading to low CO2 conversion rates. Furthermore, in Comparative Example 2, the NH2-MIL-125 loading on FTO is low, making it prone to accumulation and difficult to grow on FTO. In Comparative Example 3, the Ni-BDC on ITO is not fully spread into a dense layer, resulting in clusters; the amount of secondary-grown NH2-MIL-125 is limited and easily detaches. In Comparative Example 4, a large amount of Ni-BDC detaches from the ordinary glass slide, making it difficult to form heterojunctions when NH2-MIL-125 is loaded again. In Comparative Example 5, the NH2-MIL-125 loaded on FTO easily detaches, and compared to Example 1, the amount of Ni-BDC loaded is small, indicating weak synergy between the two.
[0081] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A nanoarray composite photocatalyst based on a metal-organic framework material, characterized in that, It includes an FTO matrix, a sheet-like Ni-BDC nanosheet array grown in situ on the surface of the FTO matrix, and NH2-MIL-125 loaded on the Ni-BDC nanosheet array; The preparation method of the nanoarray composite photocatalyst based on metal-organic framework materials includes the following steps: (1) In situ growth of Ni-BDC nanosheet array on FTO matrix surface includes the following steps: dissolving nickel salt and terephthalic acid in a mixed solution of N,N-dimethylformamide, water and anhydrous ethanol using ultrasound, then placing the FTO matrix into the mixed solution, heating, washing and drying, so that Ni-BDC nanosheet array grows in situ on FTO matrix surface. (2) The FTO matrix with Ni-BDC nanosheet arrays grown in situ on the surface was immersed in NH2-MIL-125 synthesis solution and NH2-MIL-125@Ni-BDC was hydrothermally synthesized to obtain the nanoarray composite photocatalyst based on metal-organic framework material. In step (1), the molar ratio of the nickel salt and terephthalic acid is 1:1, the volume ratio of water, anhydrous ethanol and N,N-dimethylformamide is 1:1:(10-16), and the concentration of terephthalic acid in the mixed solution is 0.03-0.04 mol / L. In step (1), the heating temperature is 90-140℃ and the time is 6-24h; In step (2), the NH2-MIL-125 synthesis solution is obtained by dissolving metallic titanium salt and aminoterephthalic acid in a mixed solution of N,N-dimethylformamide and methanol. The concentration of aminoterephthalic acid is 10-30 mmol / L, the volume ratio of N,N-dimethylformamide to methanol is 1:9-9:1, and the ratio of aminoterephthalic acid, mixed solution and metallic titanium salt is 0.22g:10mL:250μL.
2. The nanoarray composite photocatalyst based on metal-organic framework materials according to claim 1, characterized in that, In step (2), the temperature of the hydrothermal treatment is 120-150℃ and the heating time is 12-24h.
3. The application of the nanoarray composite photocatalyst based on metal-organic framework materials as described in any one of claims 1 to 2 in the catalytic reduction of carbon dioxide.
Citation Information
Patent Citations
In-situ carbon-coated copper-nickel alloy material photocatalyst and preparation method and application thereof
CN110624550A
MOF-based derived composite photocatalyst and preparation method thereof
CN111111668A